An Empirical Study of Religion and Marketing Professionals: Buddhism and Marketing Ethics - Türkmen, Hediye Gamze; Nardalı, Sinan (International Journal of Contemporary Economics and Administrative Sciences, 2025)
Religion and marketing ethics are an area of significant interest in literature that both play influential roles in shaping marketing professional’s ethical and moral standards. This study aims to examine the impact of marketing professionals’ religiousness in the context of Buddhism on ethical intentions and moral approaches and, while exploring the relationship between marketing ethics and Buddhism in a broader context. For this research, a face-to-face survey was conducted with the marketing professionals in Thimphu, the capital city of Bhutan. The data obtained from these surveys were analyzed using SPSS, applying quantitative methods such as factor analysis, correlation, and mediation analysis. The findings reveal significant positive correlations between religious emotional involvement and ethical behavior, as well as between guidance from Buddhist teachings and ethical behavior. Furthermore, demographic factors like job position and income were found to partially mediate the relationship between religious involvement and ethical behavior. These results highlight the important role that Buddhist principles play in shaping ethical decision-making in marketing, offering new insights into the intersection of religion and business ethics.